2007
DOI: 10.1152/physiolgenomics.00165.2007
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering: a new frontier in physiological genomics

Abstract: Considerable progress has been made in the last decade in the engineering and construction of a number of artificial tissue types. These constructs are typically viewed from the perspective of possible sources for implant and transplant materials in the clinical arena. However, incorporation of engineered tissues, often referred to as three-dimensional (3D) cell culture, also offers the possibility for significant advancements in research for physiological genomics. These 3D systems more readily mimic the in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…A successful comparison of gene expressions of five calcium‐handling proteins between a neonatal heart and various culturing conditions was achieved. It was concluded that culturing the cells in a three‐dimensional environment produces tissues that more closely resemble native cardiac tissue (29–31). There still needs to be a lot more research done in order to develop the perfect culturing conditions which will provide the correct and adequate amount of nutrients to each cell.…”
Section: Discussionmentioning
confidence: 99%
“…A successful comparison of gene expressions of five calcium‐handling proteins between a neonatal heart and various culturing conditions was achieved. It was concluded that culturing the cells in a three‐dimensional environment produces tissues that more closely resemble native cardiac tissue (29–31). There still needs to be a lot more research done in order to develop the perfect culturing conditions which will provide the correct and adequate amount of nutrients to each cell.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture techniques must be adapted over scaffolds with 3D architecture, designed in scales relevant to tissue natural physiologic processes [10]. The main goal of using tissue engineering in biomedical research is to combine traditional two-dimensional (2D) cell culture and in vivo conditions, submitting cultured cells to an environment that better represent the complex 3D structure of the native tissue, where cells grow surrounded by the extracellular matrix and neighboring cells in all three dimensions [11]. Therefore, we aim to perform comparative biocompatibility in vitro studies, evaluating cell cultures both in monolayer and in an organized 3D structure in order to characterize the limitations and advantages of each method, considering two different types of cells cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they have been commonly used to examine cancer cell biology and develop new drugs. However, tumor cells grown in 2D culture systems differ from those grown in vivo; they have different morphology, cell-to-cell or cell-to-matrix adhesions, cellular differentiation patterns, and cellular behaviors (3,4).…”
Section: Introductionmentioning
confidence: 99%